Peranan Atribut Ekstrinsik Merek terhadap Minat Beli Konsumen Smartphone Blackberry - Anas Hidayat; Lhia Dwi Agustin (Telaah Bisnis, 2016)
Abstract This research aims to examine the role of brand preference, luxury brand perception and country of origin in influencing consumers to buy Blackberry smarthphone, as well as to examine the role of country of origin in influencing luxury brand perception. The population of this research are students in economics faculty of Indonesia Islamic University, and the sample used is 250 respondent. This research was found that the most devotee of blackberry smartphone is women, with 53,6%, aged between 18-23 years old, with a pocket money between Rp1.000.000-Rp2.000.000 monthly and expenditure of Rp500.000-Rp1.499.999 monthly. By using Structural Equation Modeling, the results show that there are positive and significant impact on the country of origin to the purchase intention, positive and significant impact on the country of origin to luxury brand perception, positive and significant impact on the luxury brand perception to purchase intention and positive and significant impact on the brand preference to purchase intention of blackberry smartphone’s consumer in economics faculty of Indonesia Islamic University.